Glutamatergic Dysfunction and Glutamatergic Compounds for Major Psychiatric Disorders: Evidence From Clinical Neuroimaging Studies - Li, Cheng-Ta; Yang, Kai-Chun; Lin, Wei-Chen (Frontiers in Psychiatry, 2019)
Glutamate is the major excitatory neurotransmitter in the human brain. Excessive glutamate release has been linked to stress and many neurodegenerative diseases. In addition, a growing body of evidence pinpoints that abnormalities of glutamatergic neurotransmission or glutamatergic dysfunction play an important role in the development of many major psychiatric disorders (e.g., schizophrenia, bipolar disorder, major depressive disorder, and treatment-resistant depression). Recently, ketamine, an NMDA antagonist, has been demonstrated to have promisingly rapid antidepressant efficacy for treatment-resistant depression. Afterwards, many compounds that target at glutamate system are also available and possess potentials in the treatment of major psychiatric disorders. In this review, we will update evidence from recent human studies that directly or indirectly measure glutamatergic neurotransmission and function, including magnetic resonance spectroscopy (MRS), PET (positron emission tomography)/single-photon emission computed tomography (SPECT), and paired-pulse transcranial magnetic stimulation (ppTMS) on major psychiatric disorders. The newer generation of antidepressants targeting the glutamatergic system from human clinical studies is also reviewed.